Characterization of Potential Plant Growth Promoting Rhizobacteria Isolated from Maize (Zea mays L.) in Central and Northern Benin (West Africa) - Nadège A. Agbodjato; Pacôme A. Noumavo; Farid Baba-Moussa; Hafiz A. Salami; Haziz Sina; Alphonse Sèzan; Honoré Bankolé; Adolphe Adjanohoun; Lamine Baba-Moussa (Applied and Environmental Soil Science)
Our study aims to characterize Plant Growth Promoting Rhizobacteria (PGPR) isolated from maize roots in five agroecological zones of central and northern Benin. Sixty samples were collected at the rate of four samples per village and three villages per agroecological zone. Rhizobacteria strains were isolated from these samples and biochemically characterized. These strains were analyzed for some of their PGPR traits like ammonia production and hydrogen cyanide following conventional methods. Microbiological investigation of these samples has shown that maize rhizospheres in central and northern Benin contain a high diversity of microorganisms. A total of nine species of maize Plant Growth Promoting Rhizobacteria were identified. Those PGPR include five Bacillus species (B. polymyxa, B. pantothenticus, B. anthracis, B. thuringiensis, and B. circulans), three Pseudomonas species (P. cichorii, P. putida, and P. syringae), and Serratia marcescens. The microbial diversity does not depend on the soil types. The microbial density, generally high, varies according to both soil types and agroecological zones. All Serratia strains (100%) have produced ammonia, whereas 80% of Bacillus and 77.77% of Pseudomonas produced this metabolite. The hydrogen cyanide was produced by all isolates (100%) independent of their genus. These results suggest the possibility to use these rhizobacteria as biological fertilizers to increase maize production.